REVITALISASI KANDEKANDEA SEBAGAI MEDIA PELESTARIAN BUDAYA DAN PENGUATAN SOLIDARITAS SOSIAL DI MASYARAKAT BUTON - Suryanti, Suryanti; Agustina, Wa Ode (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Title of article is Revitalization of Kandekandea as a Medium for Cultural Preservation and Strengthening Social Solidarity in Buton Society Kandekandea is a traditional practice of the Buton people, where communities exchange homemade cakes as a symbol of unity and solidarity. However, due to modernization and shifting lifestyles, this tradition is gradually fading. This Community Partnership Program (PkM) aims to revitalize Kandekandea as a means of cultural preservation while reinforcing social bonds in Buton society. The methods include mentoring women’s groups, training in traditional cake-making, cultural documentation, and digital media campaigns. The expected outcomes are increased awareness among the younger generation about the importance of preserving this tradition, the growth of a creative economy based on traditional culinary arts, and stronger social networks within the community. This initiative not only safeguards cultural heritage but also empowers society socially and economically, ensuring that Kandekandea remains relevant in the modern era.